O ensino de história no ginásio do Espírito Santo durante o Estado Novo (1937-1945) - Faria, Paula Florinda de Freitas (2019)
It focuses on the configuration of the History Teaching in the Gymnasium of Espírito Santo (GES) during the Brazilian New State (1937-1945), when the Vargas’ government instituted public policies that strongly impacted the conduction of education in Brazil. Given the model character assumed by the GES in the implementation of these policies at the state level, this study investigates the developments of the guidelines for the History Teaching in the Gymnasium of Espírito Santo. It is based on theories by Historians Marc Bloch (2001) and Carlo Ginzburg (2001), especially with regard to the interrogation process and analysis of the worked sources, comprising: newspapers, legislative documents, teaching programs, exams, exams scores listing, record of the GES library collection, list of the GES teachers and textbooks adopted by the institution during the investigated period. For the analysis of textbooks, it is based on theories by Roger Chartier (2002, 2011). The final discussions indicate that, echoing the national guidelines outlined for the History Teaching during the New State, the teaching programs established in the GES prioritized content related to History of Brazil, focusing on the following topics: patriotism, historical figures, great achievements, Brazilian ethnic formation, and national feeling. Through these themes, it was intended to build a common past based on the formation of the good morals of the Brazilian citizen. The work with the sources also allowed some approximations with the teachers who taught History in the GES, both through institutional documents and eventual journalistic publications. Moreover, exams and "loose" exam scores between the analyzed documents allowed an indicted approximation to the taught contents in the GES and two other Espírito Santo institutions. In general, it is evident the attempt to expose the alignment of History Teaching to the nationally prescribed guidelines under the dictatorial government of Getúlio Vargas (1937-1945), from the absolute convergence of the addressed topics, from the textbooks and nationally adopted programs.